INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PADA KANTOR CAMAT KECAMATAN SINGKUT KABUPATEN SAROLANGUN - Dahmiri Dahmiri (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
This study entitled "Community Satisfaction Index Against the Office of head of sub district Singkut District Sarolangun". Tujun research is to know the Satisfaction Index of society Against the Office of head of sub district Singkut District Sarolangun. This research only focuses on Community Satisfaction Index Against the Office of the head of Sarolangun Regency Of Singkut Sub-district. As for specific targets to be achieved from this research is attempting to menemukanseberapa the index of satisfaction of society Against the Office of head of sub district Singkut District Sarolangun. Research methods that will be used is survey research. Activities performed are researching using the questionnaire as a tool to collect data. The model in this study is the method of observation and documentation, and Interval Scale using a detailed questionnaire and the method of determination the sample as much as 150 samples. The method used is Descriptive Qualitative. The technique analysis of the data is performed using the community's Satisfaction Index value (IKM) are calculated using the weighted average value of each item of service. The results showed that the responses of the respondents against the Office of the head of service satisfaction Singkut Regency Sarolangun average fall into the category of good. Indicators satisfaction index on Servicing Sarolangun Regency Singkut Head Office which is the highest indicator keamananpelayanan NRR 3.12 or categories with safe. Service satisfaction index indicator Head Office Singkut the lowest Sarolangun Regency is an indicator of the speed of service or categories 2.11 NRR less quickly.Keywords: Community Satisfaction Index, Services, Office Head